Development of web-based learning media with a realistic mathematics education approach to increase student self-determination - Muhammad, Iryana; Jupri, Al; Herman, Tatang (Jurnal Infinity, 2025)
This study aims to: (1) develop and validate web-based learning media utilizing Google Sites with a realistic mathematics education (RME) approach on linear inequality material in one variable that is valid and effective; (2) enhance students' self-determination in mathematics. The subjects consisted of 27 seventh-grade students from a junior high school in Lhokseumawe City, Aceh. This research employed the research and development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used include expert validation sheets, student response questionnaires on the practicality of the media, and student self-determination questionnaires. The results indicate that the web-based learning media with the RME approach on linear inequality in one variable is suitable for use and improves students' self-determination in mathematics. This study highlights the potential benefits of web-based learning with the RME approach in mathematics education.